(untitled) (Eurasian Medical Research Periodical, 2026)
Given the growing recognition of the interplay between metabolic disorders and chronic lung diseases, this study aimed to assess, based on biochemical parameters of lung tissue, the effectiveness of vegetable oils in preventing interstitial lung lesions in rats with alloxan-induced diabetes and experimental interstitial pulmonary fibrosis.